2018
DOI: 10.1038/s41598-018-19519-3
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of soil mercury accumulation by vegetables

Abstract: Mercury pollution in soil poses serious risks to human health through consumption of contaminated vegetables. We used a meta-analysis to examine the mercury enrichment ability of different vegetables and the main factors affecting mercury uptake. We drew the following conclusions. (1) Plants with a lower bioconcentration factor (BCF) include cowpea, long bean, and radish, whereas plants with a higher BCF include green pepper, spinach, cabbage, and Chinese cabbage. (2) Leaf and cucurbit have the highest and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 20 publications
1
20
0
3
Order By: Relevance
“…Our values matched with the fraction of different metals studied in two different soils (Dočekalová et al 2012). It is known that the Hg concentration in most crops is mainly in its inorganic form (WHO 1991) which is more mobile than the organic species because of the adsorption into soil particles, reducing the direct flow into the soil water (Yu et al 2018). Therefore, the use of both DGT devices allows us to know which part can be rapidly uptaken by plants in the early growth stages.…”
Section: Dgt and Lettuce Measurementssupporting
confidence: 72%
“…Our values matched with the fraction of different metals studied in two different soils (Dočekalová et al 2012). It is known that the Hg concentration in most crops is mainly in its inorganic form (WHO 1991) which is more mobile than the organic species because of the adsorption into soil particles, reducing the direct flow into the soil water (Yu et al 2018). Therefore, the use of both DGT devices allows us to know which part can be rapidly uptaken by plants in the early growth stages.…”
Section: Dgt and Lettuce Measurementssupporting
confidence: 72%
“…De Temmerman et al [46] indicate that under experimental setting, there is no evidence of any root uptake of mercury in growing leafy vegetables in a peat based substrate. Yu et al [47] examined the role of soil mercury in vegetable absorbtion. Enrichment ability was higher in green pepper, spinach, cabbage and Chinese cabbage.…”
Section: Discussionmentioning
confidence: 99%
“…Recent consumption of red vegetables, leafy vegetables, or vegetable oil was associated with higher THg among both seafood and non-seafood consumers and MeHg among seafood consumers, after adjustment for demographic variables. Several studies have suggested that leafy vegetables or other plants are able to uptake mercury as a result of local mercury contamination in soil ( 60 64 ), air ( 65 , 66 ), water ( 67 , 68 ); or from mercury-containing biosolids applied to soils ( 69 72 ). Epidemiology studies have also identified associations of vegetables with mercury biomarkers among populations living near areas with environmental mercury contamination ( 37 , 57 ), as well as populations in Korea ( 38 ) and Finland ( 35 ).…”
Section: Discussionmentioning
confidence: 99%